2021
DOI: 10.1007/s00586-021-06827-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lumbar laminectomy on spinal sagittal alignment: a systematic review

Abstract: Purpose Positive spinal sagittal alignment is known to correlate with pain and disability. The association between lumbar spinal stenosis and spinal sagittal alignment is less known, as is the effect of lumbar decompressive surgery on the change in that alignment. The objective was to study the evidence on the effect of lumbar decompressive surgery on sagittal spinopelvic alignment. Methods The Cochrane Controlled Trials Register (CENTRAL), Medline, Embase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…[16][17][18][19][20][21] However, these studies provided limited evidence on improvements of SSPA and showed various patterns of improvements. 4 Lower back pain in patients with LSS is presumably caused by buckling of the ligamentum flavum that impinges on the spinal nerves, thus impeding blood supply. This phenomenon is counteracted by flexion of the lumbar spine, which stretches the ligamentum flavum, thereby releasing the impingement causing apparent malalignment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[16][17][18][19][20][21] However, these studies provided limited evidence on improvements of SSPA and showed various patterns of improvements. 4 Lower back pain in patients with LSS is presumably caused by buckling of the ligamentum flavum that impinges on the spinal nerves, thus impeding blood supply. This phenomenon is counteracted by flexion of the lumbar spine, which stretches the ligamentum flavum, thereby releasing the impingement causing apparent malalignment.…”
Section: Discussionmentioning
confidence: 99%
“…limited evidence to support this phenomenon, and disagreements between patterns of change in SSPA parameters still exist. 4 Clinical symptoms of LSS vary widely. Most patients present with neurogenic intermittent claudication, which is aggravated during various periods of standing and walking.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the study of Hatakka (Hatakka et al, 2021), in conclusion, the quality of the evidence on the effect of decompressive surgery for spinal-pelvic alignment was low, and there was substantial heterogeneity of the study design among the studies included. In addition, few studies have been conducted on the correlation of sagittal parameters according to LIF for each pelvic type.…”
Section: Introductionmentioning
confidence: 96%
“…Previous studies evaluating the role of decompression surgery on sagittal alignment parameters have at best demonstrated a small, statistically significant but probably clinically insignificant effect on sagittal alignment parameters. 2 Most of those studies, however, focused on the presence of LSS rather than symptoms such as pain as was performed in this study. By evaluating the presence of painful degenerative conditions and demonstrating that the SSPA parameters do improve in this patient population as compared with the more general LSS population, the results provide more granularity and data addressing this interesting topic.…”
mentioning
confidence: 98%